An Investigation of the Weak Form of the Efficient Markets Hypothesis for the Kuwait Stock Exchange. (April 2018) - Almujamed, Hesham I.; Fifield, Suzanne G. M.; Power, David M.
This article investigates the weak form of the efficient market hypothesis (EMH) for the Kuwait Stock Exchange (KSE). In particular, it tests whether share returns on the KSE exhibit patterns which may be used to predict future share price changes. Ten filter rules are tested on weekly data for 42 firms over the period 1998–2011. The results suggest that the KSE was not weak-form efficient because patterns and trends were present in security prices. In addition, the results are consistent with the substantive literature which has argued that emerging stock markets are informationally inefficient, such as Fifield, Power and Sinclair (2005, 2008) and Xu (2010) and particularly those early studies of Al-Shamali (1989) and Al-Loughani and Moosa (1999) that looked at trading rules for the KSE.